Future Directions of Cytokine Hypothesis in Depression: 'NLRP3 inflamazomu' - ARICIOĞLU, FEYZA (KURE ILETISIM GRUBU A S, 2013)
The prevalence of depression has been shown to be increased with the presence of chronic inflammatory and/or autoimmune diseases such as rheumatoid arthritis, systemic lupus erythematosus, type II diabetes mellitus and cardiovascular diseases. It has been well documented in the last decade that inflammation in the periphery could interact within the central nervous system. Once an inflammatory stimulus reaches the brain, microglial cells serve as fundamental sensory complements by playing an important role in neuroinflammation which is a necessary process required for brain development. However, the process itself, if excessive or prolonged, can turn into a pathological condition and become a causative factor of the disease, for example, in the case of chronic stress or depression. The association between high plasma levels of pro-inflammatory cytokines and depression has been shown by several clinical and experimental studies. In addition, current antidepressant therapies reduce high cytokine levels of depressive patients and antidepressant-like effects are observed with the use of immunosuppressant drugs acting on cytokine-mediated mechanisms. On the other hand, inflammatory cytokines are known to mediate the activity of the hypothalamic-pituitary axis (HPA) which is well known to be elevated in depression and stress, resulting in a further contribution to the inflammatory state. At present, approximately of patients with depression do not respond to current antidepressant therapies. Thus, great efforts have been made in many studies to provide novel therapeutic approaches for depression. At this point, targeting initiator molecular mechanisms of cytokine-mediated inflammatory responses has become an intriguing approach for preventing the process before the production and release of these inflammatory mediators. Herein, we have aimed to draw attention to a novel aspect of the cytokine hypothesis of depression that may serve as a novel target mechanism and provide further understanding of the disease, namely NLRP3 inflammasome, a multi protein complex formed in macrophage and microglia cells which is responsible for initiating the inflammatory responses mediated with IL-1 beta and IL-18.
Keywords: inflammasome; depression; cytokine; pro-inflammatory; IL-1 beta; microglia; NLRP3; CENTRAL-NERVOUS-SYSTEM; INTERLEUKIN-1-BETA RELEASE; INFLAMMATORY CYTOKINES; BRAIN; EXPRESSION; MECHANISMS; RELEVANCE; NEUROPSYCHOPHARMACOLOGY; CORTICOSTERONE; METAANALYSIS